ANALISIS ZAT GIZI DAN UJI DAYA TERIMA FLAKESTEPUNG PISANG BARANGAN MENTAH DAN TEPUNG TALAS - Vella Regalia; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Banana  ‘barangan’  unripe  flour  and  taro  flour  can  be  processed  into  flakes. Flakes is fast food favored all ages by children to the adults. Flakes has a unique shape. This  research  aims  to  determine  the  acceptability  and  nutritional  content  of  flakes mixed of banana ‘barangan’ unripe and taro flour.The  type  of  research  was  an  experiment  conducted  by  completely  randomized design using three treatment, taro flour and banana ‘barangan’ unripe flour  2:1,  1:2, 1:1.  Acceptability  test  of  flakes  banana  ‘barangan’  unripe  flour  and  taro  flour  by  30 student  of   faculty  Public  Health,University  of  North  Sumatera,  nutrient  content analysis  was  tested  in  laboratory  of  Industrial  Research  and  Standarization  Agency Medan.The results  of acceptability  organoleptic test based on color, aroma,  flavor and texture by 30 panelist showed the most preferred  were flakes with of taro flour 25% and banana ‘barangan’ unripe flour 75%. The results of nutrient  content analysis  showed that  three  treatments  had  content  carbohydrates  84,4%,  79,1%,  74,0%,  content  of protein 4,97%, 5,42%, 7,18% and fat 3,34%, 2,10%, 6,41%.It is recommended for people to take banana ‘barangan’ unripe flour and taro flour to become a flakes as alternative fast food to breakfast.Keywords:  Banana  ‘Barangan’  Unripe  Flour,  Taro  Flour,  Flakes,  Acceptability, Nutrient Content